Pendidikan Ekonomi Informal Keluarga Nelayan Di Desa Palang Kabupaten Tuban - Yosia Dian Purnama Windrayadi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
This study aims to identify informal economic education in fishermen's families in the village of Palang, Tuban Regency. The focus of the research that will be addressed includes the economic condition of the family, internalized economic education for children and the impact of economic education on children's attitudes and behavior in frugal consumption and saving in fishermen's families. This study uses a descriptive qualitative research method with a phenomenological approach. The location of this research is in Palang Village, Palang District, Tuban Regency. The results of the study are that (1) The economic condition of fishermen's families is classified as middle to lower, based on the wages earned from fishing every day, still below the minimum wage of 70 thousand - 80 thousand only every day. Families are in limited conditions in meeting the needs of food, clothing and housing. To meet the household needs and education of fishermen's families, they must look for other sources of income so that they have more than one job. (2) The value of economic education instilled in children in fishermen's families is about saving, both the reasons for the importance of children's attitudes and behavior about saving, how to use pocket money, and the introduction of parents' jobs. The way parents teach the value of business education is through verbal explanations, examples and direct examples, and involving children in work so that they gain experience in the world of work. (3) Economic education has a positive or good impact on the attitudes and behavior of children in terms of frugal consumption and saving in fishermen's families. Children become more independent and disciplined in carrying out their economic activities and have good attitudes and behavior in terms of frugal consumption and saving.DOI: https://dx.doi.org/10.17977/UM014v15i12022p058